An update on diversity of sea cucumbers (echinodermata: holothuroidea) in Malaysia - Kamarudin, K. R.; Rehan, A. M.; Hashim, R.; Usup, G. (The Malayan Nature Journal (MNJ), 2010)
Sea cucumbers (Echinodermata: Holothuroidea) are regarded as an important part of Malaysia’s marine heritage due to their diversity and commercial value. Several ecological studies have been conducted aimed at documenting the distribution of sea cucumbers in Malaysia. It is estimated that more than 80 species of sea cucumber are present in Malaysia. Nevertheless, a large number of undetermined species have been recorded, thus requiring further research to update the species identification. Molecular approaches are capable of providing insights into the phylogeny of sea cucumbers and can support the outcomes of traditional morphological approaches, and a number of molecular ecological studies have been recorded in Malaysia since 1999.